1994
DOI: 10.1161/01.res.75.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Relation between myocardial function and expression of sarcoplasmic reticulum Ca(2+)-ATPase in failing and nonfailing human myocardium.

Abstract: Expression of sarcoplasmic reticulum (SR) Ca(2+)-ATPase was shown to be reduced in failing human myocardium. The functional relevance of this finding, however, is not known. We investigated the relation between myocardial function and protein levels of SR Ca(2+)-ATPase in nonfailing human myocardium (8 muscle strips from 4 hearts) and in myocardium from end-stage failing hearts with dilated (10 muscle strips from 9 hearts) or ischemic (7 muscle strips from 5 hearts) cardiomyopathy. Myocardial function was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
361
2
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(410 citation statements)
references
References 37 publications
31
361
2
16
Order By: Relevance
“…This is an obvious departure from previously published studies of HF in human patients21 or animal studies, of which large animal models utilizing dogs or rabbits have been thought to provide the most clinically useful replacements 11. Nonetheless, although large animal models present with important similarities to humans, for example, with respect to excitation contraction coupling and contractile mechanisms, they also differ with respect to aetiology and have been reported to differ in aspects of cardiac function and response to injury;52, 53, 54 see also the review by Hasenfuss 11…”
Section: Discussioncontrasting
confidence: 76%
“…This is an obvious departure from previously published studies of HF in human patients21 or animal studies, of which large animal models utilizing dogs or rabbits have been thought to provide the most clinically useful replacements 11. Nonetheless, although large animal models present with important similarities to humans, for example, with respect to excitation contraction coupling and contractile mechanisms, they also differ with respect to aetiology and have been reported to differ in aspects of cardiac function and response to injury;52, 53, 54 see also the review by Hasenfuss 11…”
Section: Discussioncontrasting
confidence: 76%
“…The accelerated relaxation that occurs with an increase in stimulation frequency remains less well understood, but recent studies suggest that not only the faster intracellular calcium decline, but also the myofilament responsiveness plays a critical role. Given the fact that the altered frequency-dependent response is a critical modulator of cardiac function, and this modulating function is severely impaired in various cardiomyopathies [57,58], a better understanding of the mechanisms underlying frequency-dependent modulation of contractility and relaxation, including post-rest potentiation and extra-systolic beat behavior, may be paramount in development of treatment of these cardiomyopathies. Comparison of the force frequency relationships in various species.…”
Section: Discussionmentioning
confidence: 99%
“…SERCA-2a has been implicated as a marker for progressive hypertrophic growth and heart failure (8). It has been suggested that a decreased level of SERCA-2a is associated with impaired uptake of Ca 2+ into sarcoplasmic reticulum and contributes to slowing of relaxation in the failing human hearts (20).…”
Section: Discussionmentioning
confidence: 99%